Global Contributions to Mental Health Research in Muslim Communities: A Bibliometric Approach to Islamic Education - Md. Ishaque; Mahmudulhassan Mahmudulhassan; Muhammad Abuzar (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study aims to analyze the trends, patterns, and thematic evolution of mental health research within Islamic or Muslim contexts, identifying key contributors, journals, institutions, and global collaborations to address existing knowledge gaps. Grounded in theories of cultural psychology and religious coping, particularly those advanced by Pargament (2001) and Koenig (2001), the study highlights the interplay between religion, spirituality, and mental health outcomes. A quantitative bibliometric analysis was conducted using data collected through a Boolean search on the Scopus database for the period 1976–2024. After filtering, the search produced 111 relevant documents, which were analyzed using R/R-Studio, VOSViewer, and Microsoft Excel to visualize document trends, keyword co-occurrence networks, and collaboration patterns. The findings reveal a steady annual growth rate of 9.75%, with significant contributions from journals such as “Mental Health, Religion and Culture” and “Journal of Muslim Mental Health.” The United States leads in research productivity while emerging nations like Malaysia and Iran show growing contributions. Key research themes include spirituality, psychological stress, stigma, mental disorders, and mental health challenges among vulnerable populations such as refugees. The study provides a roadmap for future research, emphasizing the importance of culturally sensitive and interdisciplinary approaches. This bibliometric analysis offers unique insights into the role of religion and culture in mental health research, addressing a significant gap in the literature and contributing to global scholarly efforts in this field.